(untitled) (American Journal of Islam and Society, 2006)
The “war on terror” has become one of those discursive moral high grounds that, in reality, serve as a smokescreen to conceal the imperial ambitions of a political elite. While the corporate media generally supports this elite by (mis)informing the general public about the war’s “progress,” more pertinent threats fail to attract the same kind of political attention (and general hand wringing) associated with the “green menace.” I could be referring to global warming, which some scientists consider one of the greatest threats to human life, or to the spread of such deadly diseases as the H1V avian flu virus. Actually, I am referring to organized crime and its links to biker gangs. On 8 April 2006, the worst mass murder in recent Ontario history occurred near Shedden, a small southwestern town where the bodies of eight men were found in a local farmer’s field. Police arrested five people, including a Bandido motorcycle club member. The killings were club related, as the victims were members or associate members of the club. The Bandidos are a “outlaw” biker motorcycle club, held to represent that 1 percent who engage in criminal activity. As is usually the case, this minority wreaks havoc by its members’ involvement in car/motorcycle theft, drugs, prostitution, gun trafficking, and similar criminal activities. They also contribute to gun-related deaths and maimings, drug addiction, and theft. Given this reality, biker gang-related activities are of grave concern to community health and safety. And yet the West’s public venom is mostly preserved for Muslims, most of whom are peace-loving people seeking to live quiet productive lives in safe neighborhoods. It is this overarching discourse of the supposedly “evil” scourge of Muslims against the backdrop of the more tangible, long-term, and widespread threats of organized crime that is worrying on at least two fronts. First, its demonization of Muslims makes their lives in the West an increasingly problematic experience and, second, it focuses the public’s attention on an abstract threat (“terror”) while diverting attention from more tangible (if intractable) threats, thereby allowing the United States’ neoconservative imperial ambitions to proceed. Maligning Muslims and Islam is reaching a dangerous level of acceptability in the United States and elsewhere in the West, even at the level of political discourse, and is buttressed by a largely supportive general public. The result: no-fly lists, racial profiling, and the jailing and torture of Muslims ...